Accommodating Decision-Makers Needs & Preferences in An Oil and Gas State-Owned Enterprise by SSM Based Action Research - Yananto, Hanto; Putro, Utomo Sarjono; Sunitiyoso, Yos (UI Scholars Hub, 2021)
The Covid-19 Pandemic has shifted the behaviour of decision-makers in all business processes. This situation has accelerated the process of digitizing all information, information technology, and business processes. As a subsidiary of an Oil and Gas State-Owned Enterprise in Indonesia, The SHU also has a similar SOE's bureaucracy for the approval process in business development. What factors were considered, and how did the interaction and interrelation within those factors influence the decision-making is the main question in this research. This research aims at developing the decision-making system by accommodating the decision-maker's needs and preferences. Action research based on soft systems methodology (SSM) is used to model the new decision-making system and compare results. The long decision-making stages of business development investment have delayed several important business development projects, leading to missed early production opportunities and increased capital investment. Financial decision documents have to be wet-signed by all stakeholders involved in the decision -making process. It is practically difficult to follow existing business processes for business development approval during the Pandemic. The Covid-19 Pandemic is an entry point for redefining existing decision-making systems. The results showed that the principle of prudence and compliance are the main factors influencing decision-making. The development of digital review and approval based on a decision-making system conceptual model accommodated the interests of all stakeholders, and business processes continued during the Pandemic